2021
DOI: 10.2196/23180
|View full text |Cite|
|
Sign up to set email alerts
|

Associations Between Digital Health Intervention Engagement, Physical Activity, and Sedentary Behavior: Systematic Review and Meta-analysis

Abstract: Background The effectiveness of digital health interventions is commonly assumed to be related to the level of user engagement with the digital health intervention, including measures of both digital health intervention use and users’ subjective experience. However, little is known about the relationships between the measures of digital health intervention engagement and physical activity or sedentary behavior. Objective This study aims to describe the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 58 publications
(238 reference statements)
5
66
1
Order By: Relevance
“…The mixed findings of this review are in contrast with two other reviews examining the relationship between DHI engagement and other health behaviours [ 8 , 20 ]. The first review, conducted by Donkin et al, reported a consistent positive association between DHI usage and physical health outcomes including fruit-and-vegetable intake, physical activity, weight management and reductions in smoking and smokeless tobacco use [ 8 ].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The mixed findings of this review are in contrast with two other reviews examining the relationship between DHI engagement and other health behaviours [ 8 , 20 ]. The first review, conducted by Donkin et al, reported a consistent positive association between DHI usage and physical health outcomes including fruit-and-vegetable intake, physical activity, weight management and reductions in smoking and smokeless tobacco use [ 8 ].…”
Section: Discussioncontrasting
confidence: 89%
“…This review was conducted alongside another review aiming to describe the association between DHI engagement and physical activity and sedentary behaviour with findings reported in separate publications (PROSPERO CRD 42018110657). Therefore, ‘physical activity’ and ‘sedentary behavior’ search terms were also included in the search and the results reported elsewhere [ 20 ]. We used modified versions of published search filters and used Medical Subject Headings (MeSH) or free text words for physical activity [ 21 ], dietary intake [ 22 ], DHI engagement [ 15 ] and DHIs [ 15 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…We are not aware of previous reports on the use of and attitudes towards OEC during the first COVID-19 related lockdown, and comparison with other forms of technologysupported approaches are limited. Digital health interventions and internet-delivered interventions have been shown to lead to a small but significant increase in PA [45,46]. These studies and interventions typically provide participants with various forms of support, but even so Davies and colleagues caution about the generalizability of the results if widely disseminated [45].…”
Section: Discussionmentioning
confidence: 99%
“…The findings support the value of the website within a multidelivery mode implementation intervention to support schools to implement physical activity promoting practices. Although other digital health interventions targeting physical activity have often suffered with issues of engagement [ 6 , 10 , 46 ], the website delivering implementation support for the PA4E1 program does not appear to have impaired the potential of the program to have a positive impact. As discussed by Sebire et al [ 47 ], embracing technology in school physical activity interventions may be an effective way to efficiently deliver content, for example, by reducing challenges related to limited time for training.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of engagement with digital technologies [ 4 ] may, in part, explain the modest impact of physical activity interventions that have relied on such technologies to support population-wide scale-up [ 4 , 6 , 9 ]. A recent meta-analysis of digital health interventions targeting physical activity found that higher usage engagement is associated with targeted behavior changes [ 10 ]. Perski et al [ 9 ] have conceptualized engagement with digital health interventions to include both amount, duration and depth of usage , and user subjective experience , characterized by attention, interest, and affect [ 9 ].…”
Section: Introductionmentioning
confidence: 99%